Regional variability in pregnancy and survival rates of Rocky Mountain bighorn sheep. Issue 3 (24th March 2021) - Proffitt, Kelly M.; Courtemanch, Alyson B.; Dewey, Sarah R.; Lowrey, Blake; McWhirter, Douglas E.; Monteith, Kevin.L.; Paterson, J. Terrill; Rotella, Jay; White, Patrick J.; Garrott, Robert A.
Abstract: In the Rocky Mountains, bighorn sheep restoration has been only marginally effective; this iconic wilderness species currently exists at a fraction of their historic abundance and often in fragmented and small populations. To inform bighorn sheep conservation and restoration efforts, it is critical to understand sources of variation in key vital rates. Our objectives were to characterize the spatiotemporal variations and factors affecting survival and pregnancy rates of bighorn sheep ( Ovis canadensis ) using data from 19 bighorn sheep populations in Montana and Wyoming that occupied diverse landscapes ranging from the Northern Great Plains to the Rocky Mountains. We used a hierarchical modeling approach to estimate survival and pregnancy rates of adult females and identify the important intrinsic and environmental factors affecting these vital rates. Survival of prime‐aged animals was relatively high and stable, and pregnancy rates for prime‐aged animals showed more overall variation in response to intrinsic and extrinsic factors. Summer growing season, as indexed by integrated NDVI, positively influenced the probability of pregnancy and winter survival. This highlights the important relationship between summer growing season conditions and bighorn sheep physiological status. An index of mountain lion population abundance was related weakly to winter survival of bighorn sheep, with mountain lion abundance on winter ranges negatively affecting winter survival. Our results regarding the distribution of the estimated probabilities of pregnancy and survival, and the identification of factors associated with regional variability in these vital rates provide a foundation for understanding the dynamics of bighorn sheep populations in the Rocky Mountains. The importance of summer growing season conditions suggests management efforts should focus on maintaining and improving nutritional resources on bighorn sheep summer ranges, in efforts to enhance the condition of animals entering the breeding season and nutrient‐limited winter season. Although we document nontrivial changes in both pregnancy and winter survival rates associated with environmental variation, our results broadly support the dominant paradigm of ungulate demography insofar as survival rates of adult females were relatively higher and had less variation than pregnancy rates.